Blockade Billy [compact disc, unabridged] - King, Stephen, 1947- (Audioworks/Simon & Schuster Audio, 2010)
Retired third-base coach George 'Granny' Grantham chronicles the story of Billy Blakely, a catcher called up from Iowa to play for the New Jersey Titans in the spring of 1957. A powerful hitter and passionate catcher, Blockade Billy becomes notorious for drawing blood out of runners who collide with him at home plate. However, Billy holds a sinister secret, one that causes baseball officials to remove his name from the record books.